Psychological birth trauma: A concept analysis - Sun, Xiaoqing; Fan, Xuemei; Cong, Shengnan; Wang, Rui; Sha, Lijuan; Xie, Hongyan; Han, Jingjing; Zhu, Zhu; Zhang, Aixia (Frontiers in Psychology, 2023)
Aim: To define and analyze the concept of psychological birth trauma. Design: The concept analysis method of Walker and Avant (2019) was used. Method: Eight databases (PubMed, CINAHL Complete, Cochrane Library, Web of Science, China National Knowledge Infrastructure, Wanfang, VIP Information Chinese Journal Service Platform, and Chinese BioMedicine Literature Database) were searched from inception to July 2022 for studies focused on psychological birth trauma. Results: Of the 5372 studies identified, 44 ultimately met the inclusion criteria. The attributes identified were (1) women's subjective feelings, (2) intertwined painful emotional experiences, (3) originating in the birth process, and (4) lasting until postpartum. Antecedents were divided into two groups: pre-existing antecedents and birth-related antecedents. Consequences were identified as negative and positive. Conclusion: Psychological birth trauma is a more complex and comprehensive concept than previously thought, and should be regarded as a separate postpartum mental health problem. This study deepens the understanding of psychological birth trauma through a comprehensive concept analysis and also puts forward some suggestions for the prevention, identification, and intervention of psychological birth trauma, which provides a basis for assisting in the identification of psychological birth trauma and provides a reference for the development of rigorous assessment tools and the design of appropriate interventions in the future. Further research is needed to update and refine this concept. No Patient or Public Contribution.